2017
DOI: 10.2147/ijn.s144705
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of coffee oil-algae oil-based nanoemulsions and the study of their inhibition effect on UVA-induced skin damage in mice and melanoma cell growth

Abstract: Coffee grounds, a waste by-product generated after making coffee, contains approximately 15% coffee oil which can be used as a raw material in cosmetics. Algae oil rich in docosahexaenoic acid (DHA) has been demonstrated to possess anticancer and anti-inflammation functions. The objectives of this study were to develop a gas chromatography-mass spectrometry (GC-MS) method for the determination of fatty acids in coffee oil and algae oil and prepare a nanoemulsion for studying its inhibition effect on ultraviole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 56 publications
(65 reference statements)
5
36
0
Order By: Relevance
“…Cyclin B, in complex with CDK1, triggers mitotic entry and is a key modulator of the G2/M checkpoint (21). It has been reported that coffee oil-algae oil nanoemulsions upregulated the protein level of cyclin B and downregulated the protein level of CDK1, subsequently causing cell cycle arrest of B16-F10 cells at the G2/M phase (22). By contrast, immature colon carcinoma transcript-1 knockdown downregulated the levels of cyclin B and CDK1, arresting human breast cancer ZR-75-30 cells at G2/M phase (23).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B, in complex with CDK1, triggers mitotic entry and is a key modulator of the G2/M checkpoint (21). It has been reported that coffee oil-algae oil nanoemulsions upregulated the protein level of cyclin B and downregulated the protein level of CDK1, subsequently causing cell cycle arrest of B16-F10 cells at the G2/M phase (22). By contrast, immature colon carcinoma transcript-1 knockdown downregulated the levels of cyclin B and CDK1, arresting human breast cancer ZR-75-30 cells at G2/M phase (23).…”
Section: Discussionmentioning
confidence: 99%
“…The value of the zeta potential also indicated the stability of nanocarriers in suspension. 40 For both formulations, the zeta potential was negative and showed no major changes during the 120 days of storage. The DL and EE of drug-loaded LPNs and NPs remained stable at all the time points tested in the research, indicating that the systems were stable within 4 months.…”
Section: Discussionmentioning
confidence: 92%
“…Skin permeation with the positively charged Copaiba oil NEs increased threefold the retention of the major component in copaiba oil, β-caryophyllene, in the epidermis, and also in the receptor fluid compared to the negatively charged NEs (Lucca et al 2017). Coffee oil−algae oil-based NEs with a particle size of 30 nm, zeta potential -72.72 mV, and 100% encapsulation efficiency (EE) of docosahexaenoic acid (an important component of algae oil) applied at dose of 0.1% efficiently mitigated trans-epidermal water loss, skin erythema, melanin formation, and subcutaneous blood flow in animal experiments and were found to inhibit the growth of melanoma cells B16-F10 (IC 50 : 26.5 µg/mL) and arrest the cell cycle G 2 /M phase, whereby the apoptosis pathway of melanoma cells may involve both mitochondria and death receptor (Yang et al 2017). Transdermal administration of nanogel based on optimized catechin NEs showed sustained release profile of catechin and enhanced photoprotection potential due to its improved permeability as well as bioavailability compared to the conventional gel and it could represent an effective strategy for decreasing UV-induced oxidative damage in the skin tissues (Harwansh et al 2016).…”
Section: Transdermal Nanoemulsion Formulationsmentioning
confidence: 99%